Unattended Sleep Studies in a VA Population: Initial Evaluation by Chart Review Versus Clinic Visit by a Midlevel Provider. Issue 10 (October 2016) - Alsharif, Abdelhamid M.; Potts, Michelle; Laws, Regina; Freire, Amado X.; Sultan-Ali, Ibrahim
Abstract : Objectives: Obstructive sleep apnea (OSA) is a prevalent disorder that is associated with multiple medical consequences. Although in-laboratory polysomnography is the gold standard for the diagnosis of OSA, portable monitors have been developed and studied to help increase efficiency and ease of diagnosis. We aimed to assess the adequacy of a midlevel provider specializing in sleep medicine to risk-stratify patients for OSA based on a chart review versus a comprehensive clinic evaluation before scheduling an unattended sleep study. Methods: This study was an observational, nonrandomized, retrospective data collection by chart review of patients accrued prospectively who underwent an unattended sleep study at the Sleep Health Center at the Memphis Veterans Affairs Medical Center during the first 13 months of the program (May 1, 2011–May 31, 2012). A total of 205 patients were included in the data analysis. Results: Analysis showed no statistically significant differences between chart review and clinic visit groups ( P = 0.54) in terms of OSA diagnosis. Although not statistically significant, the analysis shows a trend toward higher mean age (50.3 vs 47.4 years; P = 0.10) and lower mean body mass index (34.4 vs 36.0; P = 0.08) in individuals who were evaluated during a comprehensive clinic visit. A statistically significant difference is seen in terms of the pretest clinical probability of OSA being moderate or high in 62.2% of patients in the clinic visit group and 95.7% in the chart review group, with a χ 2 P ⩽ 0.0001. Conclusions: In the Veterans Health Administration's system, the assessment of pretest probability may be determined by a midlevel provider using chart review with equal efficacy to a comprehensive face-to-face evaluation in terms of OSA diagnosis via unattended sleep studies. Abstract : Although in-laboratory polysomnography is the gold standard for the diagnosis of obstructive sleep apnea, portable studies have been developed to help increase efficiency and ease of diagnosis, as well as access to care. This study investigated the adequacy of two different means of initial evaluation of patients who are being considered for unattended sleep studies through the utility of a midlevel provider. The investigation was performed as a retrospective chart review of consecutive patients who underwent unattended sleep studies at our institution during a specified time period.